The Joint Effects of Spatial Cueing and Transcranial Direct Current Stimulation on Visual Acuity - Taly Bonder; Daniel Gopher; Yaffa Yeshurun (Frontiers in Psychology, 2018)
The present study examined the mutual influence of cortical neuroenhancement and allocation of spatial attention on perception. Specifically, it explored the effects of transcranial Direct Current Stimulation (tDCS) on visual acuity measured with a Landolt gap task and attentional precues. The exogenous cues were used to draw attention either to the location of the target or away from it, generating significant performance benefits and costs. Anodal tDCS applied to posterior occipital area for 15 min improved performance during stimulation, reflecting heightened visual acuity. Reaction times were lower, and accuracy was higher in the tDCS group, compared to a sham control group. Additionally, in post-stimulation trials tDCS significantly interacted with the effect of precuing. Reaction times were lower in valid cued trials (benefit) and higher in invalid trials (cost) compared to neutrally cued trials, the effect which was pronounced stronger in tDCS group than in sham control group. The increase of cost and benefit effects in the tDCS group was of a similar magnitude, suggesting that anodal tDCS influenced the overall process of attention orienting. The observed interaction between the stimulation of the visual cortex and precueing indicates a magnification of attention modulation.